Answer:
[tex]f(x) =\frac{3}{\sqrt{-x}}-2[/tex]
Observe the attached image
Step-by-step explanation:
The original function is:
[tex]y =\frac{3}{\sqrt{x}}[/tex]
If we have a function g(x), then the graph of g(-x) will be equal to the graph of g(x) reflected on the y-axis.
In the same way, the graph of g(x)-2 is equal to the graph of g(x) displaced 2 units down
In this case [tex]y = g(x)=\frac{3}{\sqrt{x}}[/tex]
Then
[tex]g(-x) =\frac{3}{\sqrt{-x}}[/tex]
Finally
[tex]f(x) =g(-x)-2 =\frac{3}{\sqrt{-x}}-2[/tex]
[tex]f(x) =\frac{3}{\sqrt{-x}}-2[/tex]
The graph of f(x) is equal to the graph of [tex]y =\frac{3}{\sqrt{x}}[/tex] reflected on the axis-y and displaced 2 units downwards as seen in the attached image